Supply chain management performance and partial least square-structural equation model an application to Thai tourism supply chain - Daraka Palang (2018)
© 2018 IEEE. The assessment of tourism supply chain management performance objective in the tourism industry is to maximize satisfaction to the tourists. The objective of this research is to evaluate the impact of performance indicators on each tier of tourism supply chain from customers' perspective. The samples are 50 tourists who travelling in Thailand in 2016. The 5 Likert scales questionnaires are used in the study. This research is based on the path study of all 19 metrics of service supply chain management whereby a total of 50 foreign tourists were questioned about their opinions toward the important factors that affect service satisfaction. The analysis was done through the factor analysis and partial least square-structure equation. The data analysis helps obtain the factors used for assessing the tourism supply chain performance in the tourists' perspectives. These factors are further used to create the model and investigate the impacts of the tourism supply chain assessment. In addition, they are likely to benefit the tourism operators regarding the operational strategies and enable the tourism supply chain management effectively satisfy the tourists and survive the aggressive competition in the middle of economic downturns.